Secondary Hemophagocytic Lymphohistiocytosis With Epstein–Barr Virus-Associated Transformed Follicular Lymphoma: A Case Report and Literature Review - Xu, Huan; Xu, Xia; Cui, Guohui; Fang, Jun; Chen, Wanxin; Xue, Mei; Jin, Runming; Chen, Hongbo; Zhang, Lu; Hu, Yu (Frontiers in Oncology, 2021)
A 58-year-old male was admitted to our hospital due to lasting fever, progressive lymphadenopathy and bicytopenia, with a previously histological diagnosis of follicular lymphoma grade 3a with Epstein–Barr virus-encoded RNA positive one month ago. A second biopsy of axillary lymph node revealed concurrent diffuse large B-cell lymphoma with Epstein–Barr virus-encoded RNA positive. Another diagnosis of hemophagocytic lymphohistiocytosis secondary to Epstein–Barr virus positive diffuse large B-cell lymphoma was further concluded by clinical manifestation, laboratory test and atypical lymphocytes in peripheral-blood smear. After a pulse of steroid pre-phase treatment, the patient’s clinical condition deteriorated and died in two weeks. The presence of Epstein–Barr virus infection in patients with follicular lymphoma is associated with more aggressive clinical course and increased risk of high-grade transformation. Hemophagocytic lymphohistiocytosis in response to Epstein–Barr virus infection or lymphoma remains fatal. Early diagnosis and initiation of treatment may improve the outcome.